Effect of silver-loaded kaolinite on real ageing, hydrolytic degradation, and biodegradation of composite blown films based on poly(lactic acid) and poly(butylene adipate-co-terephthalate) - Sutinee Girdthep (2018)
© 2016 Elsevier Ltd Effect of silver-loaded kaolinite (AgKT) on real ageing, hydrolytic degradation inclusive of biodegradation of blown films of partially compatibilized poly(lactic acid) (PLA)/poly(butylene adipate-co-terephthalate) blend was investigated. Neat PLA showed the highest degradation extent, followed by the blend and the composite, respectively. The AgKT in the composite films induced crystallization, during film fabrication and hydrolysis, and acted as barrier to water adsorption, thus retarding polymer degradations. The composite film maintained its mechanical properties over a six-month ageing period with tensile strength and elongation at break as high as about 32 MPa and 140%, respectively, in transverse direction. The composite showed its biodegradation extent of 69.94% (after 90 days), conforming to the Chinese National Standard (GB/T 20197-2006) and thus offering good biodegradability for use as a material for the production of degradable plastic bags. This article demonstrated that the ageing, hydrolytic degradation, and biodegradation of PLA-based films could be tailored by AgKT incorporation. Our hypothesis on degradation phenomena at the molecular level was also suggested. Moreover, this composite formulation could be used for high-performance packaging with good biodegradability conformity.